Micromechanics-based characterization of elastic properties of shape memory polymer nanocomposites containing SiO2 nanoparticles. (July 2018) - Hassanzadeh-Aghdam, Mohammad Kazem; Mahmoodi, Mohammad Javad
In this article, a unit cell micromechanics model is developed to predict the elastic properties of shape memory polymer nanocomposites containing silica (SiO2 ) nanoparticles. The model incorporates an interphase zone corresponding to a perturbed region of shape memory polymer matrix around SiO2 nanoparticles. It is found that the elastic properties of shape memory polymer nanocomposites are significantly sensitive to the temperature in the presence of interphase region. As the temperature increases, the shape memory polymer nanocomposite elastic modulus decreases, while the normalized elastic modulus nonlinearly rises. The results reveal that Poisson's ratio decreases nonlinearly with the increase of temperature. The shape memory polymer nanocomposite mechanical properties are significantly influenced by the nanoparticle diameter in the presence of interphase region. Substantial improvement in normalized elastic modulus is observed with reducing the nanoparticle diameter. Also, a nonlinear decrease in Poisson's ratio is found as the nanoparticle diameter decreases. Furthermore, the role of nanoparticle diameter becomes more prominent due to enhancement of temperature. The results indicate that with increasing SiO2 nanoparticles' volume fraction, the elastic modulus of shape memory polymer nanocomposite nonlinearly rises, while Poisson's ratio decreases. Finally, it is shown that the increase of interphase thickness leads to the enhancement of normalized elastic modulus of shape memory polymer nanocomposite.